2023
DOI: 10.1021/acs.jpca.2c08403
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Coupled-Cluster Study on Substituent Effects in H2Activation by Low-Valent Aluminyl Anions

Abstract: The synthesis of novel aluminyl anion complexes has been well exploited in recent years. Moreover, the elucidation of the structure and reactivity of these complexes opens the path toward a new understanding of low-valent aluminum complexes and their chemistry. This work computationally treats the substituent effect on aluminyl anions to discover suitable alternatives for H2 activation at a high level of theory utilizing coupled-cluster techniques extrapolated to the complete basis set. The results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…32 Next, Villegas-Escobar, Hoobler, Toro-Labbe, and Schaefer at the Pontificia Universidad Catoĺica de Chile and the University of Georgia examined the reactivity of low-valent aluminyl ions toward H 2 through a series of coupled cluster calculations. 33 They found that aluminyl systems with carbonand nitrogen-based chelating centers would serve well to activate hydrogen without dimerization. Finally, according to a report by Datar, Wright, and Matthews at Southern Methodist University, the presence of electric fields yields shifts in absorption energies and intensities in X-ray Stark spectra that may be attributed to responses in the molecular orbitals, the dipole moment, and the geometry.…”
Section: Chemistrymentioning
confidence: 89%
See 1 more Smart Citation
“…32 Next, Villegas-Escobar, Hoobler, Toro-Labbe, and Schaefer at the Pontificia Universidad Catoĺica de Chile and the University of Georgia examined the reactivity of low-valent aluminyl ions toward H 2 through a series of coupled cluster calculations. 33 They found that aluminyl systems with carbonand nitrogen-based chelating centers would serve well to activate hydrogen without dimerization. Finally, according to a report by Datar, Wright, and Matthews at Southern Methodist University, the presence of electric fields yields shifts in absorption energies and intensities in X-ray Stark spectra that may be attributed to responses in the molecular orbitals, the dipole moment, and the geometry.…”
Section: Chemistrymentioning
confidence: 89%
“…Using restricted active space configuration interaction (RASCI) wave functions, Rodríguez-Jiménez, Carreras, and Casanova at the Donostia International Physics Center in Spain explore the origin of these couplings and introduce a new definition of the SOC constant for molecular aggregates . Next, Villegas-Escobar, Hoobler, Toro-Labbé, and Schaefer at the Pontificia Universidad Católica de Chile and the University of Georgia examined the reactivity of low-valent aluminyl ions toward H 2 through a series of coupled cluster calculations . They found that aluminyl systems with carbon- and nitrogen-based chelating centers would serve well to activate hydrogen without dimerization.…”
Section: State-of-the-art Applications Of Quantum Chemistrymentioning
confidence: 90%
“…In an earlier study with the lighter alkali metal aluminyls [AM{Al(NON Dipp )}] 2 [AM=Li ( I‐ Li), Na ( I ‐Na), K ( I ‐K)], [6b,c] the efficiency of dissociating the H−H bond at 1.5 bar pressure illustrated a diminishing trend on descending the group, requiring elevated temperatures (100 °C) and long reaction times (Li=3 days, Na=14 days, K=25 days) to achieve complete conversion [6b] . There are possibly several factors behind the harsher reaction conditions required on descending group one, but the stronger electronegativity at the top of the group is likely to be a factor in the higher reactivity of the lighter metal complexes with H 2 [8h,i] . Hence, we postulated that alternative hydride sources containing breakable C−H and Si−H bonds such as in 1,4‐cyclohexadiene (1,4‐CHD) and phenylsilane (PhSiH 3 ) may provide other oxidative addition routes to the bimetallic hydrides.…”
Section: Introductionmentioning
confidence: 99%